The necessity for the formulation of an online family dispute resolution management framework in Malaysia - Kamaruddin, Zaleha; Abdul Manaf, Zati Ilham; Abdul Kadir, Nadhilah (Kulliyyah of Information and Communcation Technology, International Islamic University Malaysia, 2020)
This article discusses the need for the formulation of an online family dispute resolution management framework in Malaysia. One of the main reasons is that young married couples need assistance to resolve challenges that they faced in their marriage. Researches have shown that the first five years is the most difficult period in a marriage. An initial study conducted by National Population and Family Development Board also known as Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN) has shown that in 2014, more than one third of a first marriage that were less than 5 years ended in divorce or separation. With the prominent role that technology plays in our society, it is hypothesized that the internet can be used as a tool to reach out to couples who are experiencing marital discords. Professional intervention is often needed to address such disagreements before it escalates into separation or divorce. Through a survey of literatures and a series of discussions gathered from workshops, it has been found that a more effective method of outreach is needed for younger couples in Malaysia who are in need of professional marital advice. This article therefore proposes for the use of an online family dispute resolution management framework as an outreach tool which can connect marriage professionals and couples who are in need of professional intervention. This Online Dispute Resolution framework will act as a guided pathway of information and advice to young couples who are considering separation or divorce.